Analisis Dampak Kebijakan Deviden dan Struktur Modal terhadap Nilai Perusahaan Farmasi di Bursa Efek Indonesia periode 2019 - 2023 - Reynita Agustina Simangunsong; Endah Supeni P; Sodikin Sodikin (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This study aims to determine the influence of dividend policy, capital structure, and investment decisions on firm value. The independent variables used in this study are dividend policy (measured using DPR), capital structure (measured using DER), and investment decisions (measured using PER). The dependent variable used in this study is firm value (measured using PBV). The population in this study consists of pharmaceutical companies listed on the Indonesia Stock Exchange with an observation period of 2019-2023. Based on the criteria set, the number of companies that meet the criteria is 8 companies. The sampling technique used is purposive sampling. The analysis method used to test the proposed hypothesis is multiple linear regression analysis. The results of this study indicate that dividend policy measured using DPR partially has a significant positive effect on firm value, capital structure measured using DER partially has a significant positive effect on firm value, and investment decisions measured using PER partially have a significant positive effect on firm value.